OCCURRENCE OF HIGH MOLECULAR WEIGHT LIPIDS (C80+) IN THE TRILAMINAR OUTER CELL WALLS OF SOME FRESHWATER MICROALGAE. A REAPPRAISAL OF ALGAENAN STRUCTURE - Allard B.; Rager M.N.; Templier J. (My University, 2002)
The purified cell walls of mother cells (CWM) were isolated from three strains of trilaminar sheath (TLS)- and algaenan-containing freshwater microalgae Chlorella emersonii, Tetraedron minimum and Scenedesmus communis. The chemical structures of CWM and algaenans were investigated by means of tetramethylammonium hydroxide (TMAH) hydrolysis and tetramethylammonium hydroxide thermochemolysis. The compounds released were characterised by 1H and 13C-NMR, gel permeation chromatography and desorption chemical ionisation mass spectrometry. The results show that the outer cell walls of the microalgae are constituted, at least in part, of linear (poly)esters containing extremely long chain alcohol and acid moieties (up to C80) and that algaenans are mainly composed of extremely long chain (di)carboxylic acids up to C120. The present results which are in direct contrast to the previous three-dimensional architecture proposed for algaenans, led us to re-interpret the algaenan structure.